Hypogonadism in male thalassemia major patients: pathophysiology, diagnosis and treatment - de Sanctis, Vincenzo; Soliman, Ashraf T; Yassin, Mohamed A; Di Maio, Salvatore; Daar, Shahina; Elsedfy, Heba; Soliman, Nada; Kattamis, Christos (Acta Biomedica Atenei Parmensis, 2018)
Failure of pubertal growth, delay or absence of sexual development, infertility and sexual dysfunction due to hypogonadism and defective spermatogenesis are frequent and well recognized disturbances among male patients with transfusion dependent (TD) thalassaemia major (β-thal). These problems are attributed mainly to the damage caused by chronic anaemia and the deposition of excess iron in the pituitary gland and testicles. This is a short review of male pubertal disorders in patients with β-thal written by pediatric endocrinologists and haematologists with an interest and active involvement, in the diagnosis and management of these complications in this group of patients. A vigilant clinical evaluation of growth and puberty, as well as an appropriate hormonal evaluation in poly-transfused (TD β-thal) patients is strongly recommended for early detection and treatment of endocrine dysfunction. Of crucial importance also, is the implementation of an efficient chelation regime from early life, to prevent severe iron load and permanent damage to the endocrine glands, particularly those responsible for gonadal function.